Pengembangan Model Green Human Resource Development untuk Penguatan SDM Inovatif dan Berkelanjutan dalam Mendukung Indonesia Emas - Rizky Indra Saputra; Jessica Alleysha Cristie Simbolon; Muhammad Rifqy (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to develop a conceptual model of Green Human Resource Development (GHRD) as a strategic approach to strengthening innovative and sustainable human resources in support of Indonesia’s Vision 2045. The research employs a qualitative approach through a systematic literature review of 20 reputable academic articles indexed in Scopus, Web of Science, and SINTA from 2020 to 2024. The data were analyzed using thematic analysis to identify key patterns, relationships, and success factors in GHRD implementation. The findings indicate that GHRD consists of three main components: green competency development, green leadership and reward system, and green organizational culture, which interact synergistically to form a green talent ecosystem. This ecosystem enhances green innovation capability, environmental performance, and workforce readiness for the green economy transition. The study contributes theoretically by offering a context-specific GHRD model for Indonesia and provides practical implications for policymakers and organizations in designing sustainable human resource development strategies.